Decision Support System for Employee Employment Remains Using Profile Matching Method in PT. Hyper Mega Shipping - Frasstio Agustin; Santoso Setiawan (Kresnamedia Publisher, 2020)
The company is a place of production where humans function as a driving force and executor to realize the company's goals that have been set previously. Every employee in a company must always try to improve their abilities and achievements. So he can get a good career path according to his dream. To facilitate the implementation of each employee's permanent employee appointment process, a decision support system is created to facilitate the process. One of the methods used in making decisions on the appointment of permanent employees is Profile Matching. The decision support system for the Profile Matching and gap analysis process is based on data at PT. Hyper Mega Shipping, Profile Matching Method is carried out to determine the appointment of permanent employees based on two aspects, namely Performance and Work Culture. The selection process results are in the form of a final employee score as a recommendation for decision-makers to determine which employees will get the promotion of permanent employee appointments.